Students’ Ability in Understanding Simple Past Tense through Whisper and Write Game - Opik Dwi Indah (Institut Agama Islam Negeri Palopo, 2019)
This research applied pre-experimental research. The research aimed at finding out whether whisper and write game can increase students’ ability in understanding simple past tense or not. The population of this research was the second grade students of Informatics Department at Cokroaminoto Palopo University. The researcher used purposive sampling technique in determining the students as sample. The sample was class 2F which consisted of 35 students. The instrument of the research was written test. The result shows that the mean score of the posttest is higher than mean score pretest (71.31 > 44.51). Meanwhile, P-Value is 0.00 and α is 0.05. It shows that P-value is smaller than α (0.00 < 0.05). It means that null Hypothesis (H0) is rejected and alternative Hypothesis (H1) is accepted. So, there is significant difference between the result of pretest and posttest after giving the treatment in teaching simple past tense by using whisper and write game. It can be concluded that whisper and write game can increase students’ ability in understanding simple past tense.